Who appropriates centrality rents? The role of institutions in regulating social networks in the global Islamic finance industry - Gözübüyük, Remzi; Kock, Carl; Ünal, Murat (Springer Nature, 2018)
This study explains and tests the effects of country-level institutions on the distribution of centrality rents between two sets of actors in an interorganizational network. Building on the literature on corporate elites, we propose that a cohesive elite following organizational logics other than profit-maximization diverts centrality rents and induces costs on firms, and that macro institutions act as external governance mechanisms to shape this relationship. We develop our theory in the emerging Islamic finance industry, where “Shariah scholars” connect firms and constitute a religious corporate elite. While central scholars in this network create legitimacy for firms, they also shirk and cause information leakage, suggesting a negative centrality-performance relationship for the firms. Country-level institutions such as government regulation and democracy, we argue, ameliorate these effects by influencing this religious elite’s institutional logic and restraining their actions, while institutions developed from within the industry strengthen the power of the elite. Testing our theory in a network of 367 scholars and 396 institutions over 31 countries using multi-level methods, we indeed find a negative centrality-performance relationship that is ameliorated by stronger government regulation but exacerbated by better-developed industry-specific institutions, as well as a negative relationship between democratic and regulatory institutions and centrality.
Keywords: 53 Ciencias Económicas::5311 Organización y dirección de empresas; ODS 10 - Reducción de las desigualdades; network theory; institutional environment; firm performance; corporate governance; networks; emerging markets; multi-level analysis